A comparative study of pellets, sinter and mixed ferrous burden behaviour under simulated blast furnace conditions. (21st April 2021) - Gavel, Dharm Jeet; Adema, Allert; van der Stel, Jan; Peeters, Tim; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
ABSTRACT: Physicochemical behaviour of the pellets, sinters and its mixture (60% pellets: 40% sinter) is investigated by a series of smelting and quenching experiments. For all ferrous raw-material beds, three distinct stages of bed shrinkage occur due to indirect reduction, softening and melting. However, the characteristic nature (displacement, temperature and permeability) differ with the ferrous raw-material type. In mixed ferrous bed, the first and third stages are found to be controlled by the pellets (individual particle shrinkage) and sinter (slow melting rate), respectively. Second stage behaviour is initially observed to be close to the pellet and later to that of sinter. In mixed bed (upto 1505°C), the interaction between the pellet and sinter is limited to the interface only. The sinter slag is observed to control the melting and dripping properties of the mixed bed.These results gives an understanding of individual and mixed burden behaviour under blast furnace conditions.